Heterotopic tubal pregnancy with a naturally conceived live twin intrauterine pregnancy in a patient with systemic lupus erythematosus: A case report - Thomas Ntounis; Zacharias Fasoulakis; Antonios Koutras; Michail Diakosavvas; Arzou Bourazan; Athanasios Pagkalos; Athina A. Samara; Emmanuel N. Kontomanolis (Case Reports in Women's Health, 2021)
Heterotopic pregnancy (HP) is defined as the simultaneous occurrence of an intrauterine and extrauterine gestation. Risk factors contributing to this condition are similar to those which contribute to ectopic pregnancy. While a triple heterotopic gestation through natural conception is uncommon, here we present the case of a patient with spontaneous intrauterine twins and a concurrent tubal extrauterine gestation, where the patient also had systemic lupus erythematosus. During the seventh week of gestation, the patient presented with acute abdomen signs and hemodynamic instability; a decision was taken to perform an emergency laparotomy. Haemoperitoneum, a total torsion of the right ovary with salpinx, a ruptured tubal pregnancy and subsequent necrosis were found intraoperatively. The patient was discharged on the sixth postoperative day and monitored throughout her whole pregnancy, with the intrauterine pregnancy progressing uneventfully. Two healthy neonates were delivered by cesarean section at 36 weeks of gestation. In conclusion, physicians treating women of reproductive age should be aware of possible HP, even in the absence of risk factors.